2022
DOI: 10.3389/fmars.2022.911731
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries

Abstract: During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams (Mercenaria mercenaria) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…These drivers, however, can also transform habitats and ecosystems in ways that harm fisheries, even if not as direct “stressors,” for instance via the promotion of harmful algal blooms (DĂ­az et al, 2019; Gobler et al, 2017; Griffith et al, 2019), the loss of seagrass habitat (Nyström et al, 2012; Strydom et al, 2020), or increased impacts of disease (Ford & Chintala, 2006; Pearce & Balcom, 2005). While climate change mitigation will require a global effort, identifying pathways toward the recovery of highly impacted hypoxic systems (Conley et al, 2009; Gobler et al, 2022; Steckbauer et al, 2011) may benefit vulnerable fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…These drivers, however, can also transform habitats and ecosystems in ways that harm fisheries, even if not as direct “stressors,” for instance via the promotion of harmful algal blooms (DĂ­az et al, 2019; Gobler et al, 2017; Griffith et al, 2019), the loss of seagrass habitat (Nyström et al, 2012; Strydom et al, 2020), or increased impacts of disease (Ford & Chintala, 2006; Pearce & Balcom, 2005). While climate change mitigation will require a global effort, identifying pathways toward the recovery of highly impacted hypoxic systems (Conley et al, 2009; Gobler et al, 2022; Steckbauer et al, 2011) may benefit vulnerable fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…In both Sedge and Quogue regions, a neighboring control site (50 m distance from reefs; SC and QC respectively) was also identified and monitored to provide measures of ambient seawater to be compared to reef‐modified seawater (Figure S1). Control locations were intentionally sited near to the outer edge of the reefs and were not proximate to any special features (i.e., inlets, freshwater inputs, or bathymetric features) that might create artificial biogeochemical differences unassociated with the reefs (Gobler et al, 2022; NOAA, 2020; USACE, 2004). Previous research and investigation during the reef permitting process also indicated no differences in water quality or sediment types between the reef sites and their respective control sites prior to the installation of the reefs (NYSDEC, 2017; Psuty & Silveira, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Shinnecock Bay is a 39 km 2 shallow tidal lagoon on the south shore of Long Island, NY, USA (Figure S1) that since the 1970s experienced declines in water quality, seagrass cover, and shellfisheries, coincident with intensifying eutrophication (Gobler & Sunda, 2012;NYSDEC, 1970NYSDEC, -2020NYSDEC, , 2009Weiss et al, 2007). Reef restoration is one component of a multidimensional restoration effort that began in 2012 and aims to improve water quality and reestablish bivalve shellfisheries by establishing hard clam spawner sanctuaries, planting eelgrass, harvesting aquacultured seaweeds, and constructing remotely set subtidal reefs (Gobler et al, 2022). (Callam & Supan, 2018) in multiple large 2000-L tanks filled with mesh bags (57 cm × 24 cm) of air-cured surf clam shell at the Stony Brook-Southampton Marine Lab.…”
Section: Site Description and Restoration Backgroundmentioning
confidence: 99%
“…For instance, blue mussel ( Mytilus edulis ) farming operations are considered cost‐effective measures for nutrient extraction and water clarity enhancement in the Baltic Sea (Gren et al., 2009; Kotta et al., 2020; Lindahl et al., 2005; Schröder et al., 2014). Bivalve‐mediated N regulation may be particularly important in vegetated coastal ecosystems, such as salt marshes, mangrove forests, and seagrass meadows, where synergistic interactions between bivalve populations and macrophytes may govern N sequestration pathways (Gagnon et al., 2020; Gobler et al., 2022). As applications of bivalve bioremediation grow, new calls to evaluate how bivalve densities modify N pools and processes across multiple scales have surfaced (Kellogg et al., 2014; Testa et al., 2015).…”
Section: Introductionmentioning
confidence: 99%